Coping Stress Konselor Pemula di SMP Negeri 10 Kota Madiun - Rahayu, Dwi Sri (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2021)
The purpose of this study was to determine the description of stress, the factors that influence it and how to cope with stress that is owned by novice counselors at SMP Negeri 10 Madiun City. The research sample was guidance and counseling teachers at SMP Negeri 10 Madiun City who had a working period of less than 2 years totaling 3 people. This study uses a descriptive qualitative pattern. The datacollection technique used is interviews. The results of the study were analyzed using the Miles and Huberman technique. From the results of the study, it is known that the sample feels stress at the beginning of their working period which is indicated by physical, emotional, interpersonal, and intellectual symptoms. Factors that affect their stress include the acceptance of colleagues, personal problems outside of work that are brought into the world of work, and feel the workload is high. Coping stress used is by venting to friends, trying to show co-workers that he has a qualified work ethic, motivating himself by believing that being a BK teacher is something to be proud of. Based on these findings, it can be concluded that novice counselors have stress disorders at the beginning of their careers and are able to manage the stress they experience with seeking social support and positive reinterpretation techniques. This is also inseparable fromhow the efforts of senior counselors who are in the workplace are able to guide and support the performance of their juniors in order to carry out their professional duties effectively.